The Development of Cultural Entrepreneurs to Cultural Enterprise for Economic Level Enhancement of the Creative District of Chiang Rai Old Town - Chumpa, Natthida; Chaiphawang, Kasidit; Piamsuwannakit, Sutthiporn; Leeniwa, Jindapa; Niwarat, Krittina (Business Administration and Economics Review, 2025)
This research aimed to analyze the potential of cultural entrepreneurs, to enhance entrepreneurial skills and to push the group together to create a network of cultural entrepreneurs to become cultural enterprise. Data were collected by using an interview form with 10 cultural entrepreneurs, partners and network of educational institutions provincial culture, community, artists, local government organizations and 15 academicians, group discussion and workshops to enhance entrepreneurial skills to become cultural enterprise of the creative district of Chiang Rai Old Town. The study was analyzed by content analysis. The results showed that the potential of cultural entrepreneurs in the Chiang Rai old town. As for the strength point, Chiang Rai was a historic old town as well as many artists. The cultural resources could be used to build an economy and the entrepreneurs were also ready to learn and adapt. As for the weakness, the organizations have not been well-known, lack of unique products, running a defensive business, lack of skills in product and business management, lack of public relations and technology skills and network connection. Additionally, the opportunity, Chiang Rai Province was a tourist destination and online marketing trends push cultural products available for sale. In terms of the threat, the spread of the COVID-19 virus has reduced the number of tourists. In addition, the cultural entrepreneurial skills enhancement was done by (1) determining target customer groups; (2) naming the organization and brand name; (3) developing management skills; (4) establishing a group of entrepreneurs and providing more skills training (5) preparing E-catalog and (6) producing video media to publicize entrepreneurs pushing for a group to build a network of cultural entrepreneurs to become cultural enterprises by linking products to exhibit, providing services or distributing to flower shop, restaurants, coffee shops, bakeries, government agencies, private sectors, temples, communities and tourists for further enhancement to the community economy in the Chiang Rai Old Town.